LABORATORY APPLICATIONS IN WASTEWATER TREATMENT BY USING FLOCCULATION PROCESS - NARCIS BARSAN; MARIANA TURCU; VALENTIN NEDEFF; EMILIAN MOSNEGUTU; DANA CHITIMUS (Journal of Engineering Studies and Research)
In the application of coagulation and flocculation process in the wastewater treatment, the laboratory activities are very important and sometime even indispensable. These activities provides some solutions to the efficiency that can be obtained and offer the possibly of results extrapolation to the industrial applications. The present study attempted to verify some possible laboratory application of the Acefloc organic flocculants series to the municipal waste leachate treatment. In these sense, some laboratory techniques were implemented to evaluate de flocculants efficiency by analyzing some quality parameters. In the case of Acefloc 00303L flocculants use were obtained the best performances regarding the analyzed quality indicators reduction. By using the flocculation process, the COD concentration decrease with 85.35 % in the case of Acefloc 00303L flocculants use